The Influence of Investment Knowledge and Risk Tolerance on Stock Investment Interest among Generation Z (A Case Study of FEBI UINSU Students) - Ridho Feriyanly; Fitri Hayati; Aqwa Naser Daulay (Value Added : Majalah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of investment knowledge and risk tolerance on stock investment interest among students of the Faculty of Islamic Economics and Business at Universitas Islam Negeri Sumatera Utara who belong to Generation Z in the 2024/2025 academic year. The research uses an associative quantitative approach through a survey of 100 respondents determined using the Slovin formula from a population of 4,553 active students. Data were collected through a Likert scale questionnaire from 1 to 5 and analyzed using multiple linear regression with the help of SPSS version 27. The results indicate that investment knowledge and risk tolerance have a positive and significant effect on stock investment interest both partially and simultaneously. The findings indicate that students’ knowledge of the concepts of risk and return makes them more prepared to face stock price fluctuations. When students have knowledge about risk and potential returns and feel comfortable with stock price movements, their interest in stock investment reflected in the intention to increase stock investment in the future tends to be stronger